2020
DOI: 10.1186/s12903-020-01165-9
|View full text |Cite
|
Sign up to set email alerts
|

Two-body wear of occlusal splint materials against different antagonists

Abstract: Background This study aimed to demonstrate that the material of the occlusal splint can be chosen according to the needs of individual patients and contribute to the knowledge of the wear rate of these materials. Methods In this study, four occlusal splint materials (Sr Ivocap Heat Cured, Valplast, SR Ivocap Elastomer and Eclipse) and three antagonists (natural tooth enamel, inCoris TZI and IPS e.max Press ceramic materials) were used. Each wear test was performed using a chewing simulator (n = 16; test load:… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
2
0
5
Order By: Relevance
“…To date, there are variety of commercial materials besides PMMA that are available for fabricating occlusal splints including polyamide resin, ethylene vinyl acetate, polycarbonate, urethane dimethacrylate. Previous studies have reported different wear resistance patterns with different occlusal splint materials [ 14 , 25 , 26 ]. In addition, fabrication methods have also shown to produce an impact on the wear resistance of occlusal splint materials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are variety of commercial materials besides PMMA that are available for fabricating occlusal splints including polyamide resin, ethylene vinyl acetate, polycarbonate, urethane dimethacrylate. Previous studies have reported different wear resistance patterns with different occlusal splint materials [ 14 , 25 , 26 ]. In addition, fabrication methods have also shown to produce an impact on the wear resistance of occlusal splint materials.…”
Section: Discussionmentioning
confidence: 99%
“…Cycle frequency was programmed for 1.42 Hz and temperature of the simulator chamber was set at 25 °C [ 12 ]. Half of the dentin-exposed tooth specimens ( n = 6) were tested at 30,000 loading cycles, while the other half at 60,000 loading cycles to resemble different number of bruxism cycles in bruxing patients [ 13 , 14 ].
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…A quantidade de corpos de prova destinados aos testes tribológicos, as dimensões da área (10 mm²) e espessura (3,3 mm), assim como a inclusão em acrílico, foram determinadas com base em estudos prévios 25,[28][29][30] .…”
Section: Microdureza Superficial E Perfil De Desgasteunclassified
“…O acabamento e polimento superficial reduzem as irregularidades superficiais do material, possivelmente melhorando a longevidade e, consequente, a resistência ao desgaste do mesmo, como evidenciado em estudos prévios (25,28,29), onde superfícies mais rugosas apresentaram maior perda de volume quando submetidas aos testes tribológicos.…”
Section: Microdureza Superficial E Perfil De Desgasteunclassified
See 1 more Smart Citation